STRUCTURE OF TROOPS DURING THE RULE OF THE BABURIDS (American Journal of Pedagogical and Educational Research, 2025)
This article describes the composition, structure, types of troops, the positive aspects of officials during the rule of the Baburids in Middle Asia, of the Middle Ages.